(3QSGdI aj GdRGjQLIs ((3jMji Hf MSjf oeUWai s)
(3ChdgG (B:s
(3GYde CjgG GdSGFd Yf CMhGd GdRGjQLI Gfc EPG CQOJ Cf JSJNQL efgG LhGHkG Yf SDGd aJVY GdbWH eHShWkG s
(3BNQgG (B:s
(3CYfj MQha GdoeKdKGJ GdCQHY Ydi GdQjH cd MQa bHd HYOg hGddg CYde HeG aj GdZjH s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3GdehUd (B(482) s
Keywords: (3GdMQha h GdChaGbs